FIRM SIZE AS A CONTROL VARIABLE IN THE EFFECT OF PROFITABILITY ON STOCK PRICE WITH CAPITAL STRUCTURE AS MEDIATOR - Istiqomah, Atika Rizki; Ichwanudin, Wawan; Suryani, Emma (Management Science Research Journal, 2023)
Purpose: The objective of this research is to figure out the impact of profitability (X) on stock prices by using capital structure (Z) as a mediating controllable and firm size as a predictor (Y). Methodology/approach: This study's population comprised eighteen companies, and it engaged secondary data and causal associative research methods with a quantitative approach. The regression intervention data analysis technique was used the SPSS 22 software. Results/findings: According to the analyses, ROA seemed to have a positive significant impact on stock prices, whereas DER had quite a significant negative impact on stock prices.Limitations: For five years, this sample was using one sub-sector of textile and garment companies. Contribution: Investors are expected to pay focus on aspects of profit related to net profit got each period based on managerial implications. Then, investors must consider the company's debt and equity levels, because companies with high debt levels can be risky to invest in. Novelty: Even though previous researchers' study became inconstant, the authors add debt to equity ratio as a mediator factor and firm size as a control framework in this research.